The contamination of hospital water supply systems by Legionella pneumophila - I. S. Tartakovsky; O. A. Gruzdeva; S. O. Sharapchenko; N. I. Gabrielyan (Вестник трансплантологии и искусственных органов, 2021)
The risk of severe infectious complications associated with provision of medical care continues to be a pressing issue in modern surgery. Legionella pneumophila, characterized by its wide distribution in water supply systems and is highly active in film formation, represents a dangerous/important cause of hospital-acquired pneumonia. Patients requiring immunosuppression, including organ transplant recipients, are in the special risk group. Prevention of hospital-acquired legionellosis in patients at risk is essential due to severe clinical manifestations and high mortality. Objective: to summarize the practical experience in detecting contamination of water supply systems by Legionella pneumophila strains in multidisciplinary hospitals in Moscow. Materials and methods. Isolation of Legionella pneumophila strains from water and biofilms of water supply systems in multidisciplinary hospitals in Moscow and serotyping of this pathogen using bacteriological, molecular genetic and enzyme immunoassay methods. Results. Legionella pneumophila content in water reached high levels. The peculiarities of Legionella pneumophila contamination of hot water supply systems included formation of stable biofilms, in which other hospital-acquired pathogens were also identified. The share of Legionella pneumophila «SG 1», which causes up to 80% legionellosis cases in the world, was 13% in the water of the hospitals surveyed. The most effective measures for prevention of legionellosis are actions aimed at ensuring water biosecurity. Conclusion. There are potential risks of disease in the surgical wards of hospitals providing medical care, including in immunocompromised patients. Due to potential risks, prevention of hospital-acquired legionellosis is a necessary component of ensuring the safety of treatment for immunosuppressed patients.